2011
DOI: 10.1158/1538-7445.am2011-lb-45
|View full text |Cite
|
Sign up to set email alerts
|

Abstract LB-45: High aldehyde dehydrogenase activity is a marker for normal hematopoietic stem cells but not leukemic stem cells in acute myeloid leukemia: novel therapeutic implications.

Abstract: Only a minority of cells, the leukemic stem cells (LSC), within AML are responsible for tumor growth and maintenance. Many patients experience relapse after therapy which originates from outgrowth of therapy resistant LSC. Therefore, eradication of LSC is necessary to cure AML. Both the normal hematopoietic stem cells (HSC) and LSC co-exist in the bone marrow (BM) of AML patients and success of anti-LSC strategies relies on specific elimination of LSC while sparing HSC. LSC are contained within the CD34+CD38-,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…For the other stem cell markers high specificity and stability during treatment/disease still have to be confirmed. The established differences in ALDH activity between CD34 + CD38 -LSCs and CD34 + CD38 -HSCs were confirmed using this aberrant marker approach [114,115], thereby strengthening that the functional ALDH assay offers an alternative tool for CD34 + CD38 -LSC identification, which importantly, could be applied in absence of aberrant antigen expression. In contrast, the SP phenotype does not discriminate between HSCs and LSCs since both may be present in the SP compartment.…”
Section: Identification Of Leukemic Stem Cellsmentioning
confidence: 57%
See 2 more Smart Citations
“…For the other stem cell markers high specificity and stability during treatment/disease still have to be confirmed. The established differences in ALDH activity between CD34 + CD38 -LSCs and CD34 + CD38 -HSCs were confirmed using this aberrant marker approach [114,115], thereby strengthening that the functional ALDH assay offers an alternative tool for CD34 + CD38 -LSC identification, which importantly, could be applied in absence of aberrant antigen expression. In contrast, the SP phenotype does not discriminate between HSCs and LSCs since both may be present in the SP compartment.…”
Section: Identification Of Leukemic Stem Cellsmentioning
confidence: 57%
“…Normal stem-and progenitor cells have high ALDH expression [109][110][111][112]. It has to be emphasized that it has recently been demonstrated that the population of cells with intermediate ALDH activity appeared to be enriched for leukemic CD34 + CD38 -cells [113][114][115]. Several authors have confirmed the leukemia initiating capacity of these cells in NOD/SCID mice [116][117][118].…”
Section: Definition Of Leukemic Stem Cellsmentioning
confidence: 97%
See 1 more Smart Citation